Review on Oxide Formation and Aluminum Recovery Mechanism during Secondary Smelting - Osoba, Lawrence Opeyemi; Owolabi, Oluwasegun Biodun; Talabi, Segun Isaac; Adeosun, Samson Oluropo (Journal of Casting & Materials Engineering, 2018)
The remelting, refining, and casting process of aluminum alloys often generate aluminum dross containing primarily oxides and nitrides of aluminum and entrapped metallic aluminum at the surface of the molten metal as a result of reactions within the furnace atmosphere at elevated temperatures. The handling of dross is an expensive but necessary activity during aluminum smelting. Furthermore, the amorphous Al2O3 oxide film formed on the pure molten aluminum surface due to the liquid metal randomly distributed atoms is impermeable to the diffusion of aluminum metal and oxygen. In amorphous materials, there is a low mobility of the charge carriers and an absence of preferred diffusion paths. This film can transform to crystalline Al2O3 by nucleation and grows with time and opportunity. This review discusses the mechanism of oxide formation and the aluminum metal recovery processes.